The Influence Of Knowledge Of Respiratory Diseases And Pulmonary Function Risks On Malaysian Adults Smoking Initiation: A Moderated Model Of Socio-Demographic Factors (International Journal of Environmental Sciences, 2025)
This study explores the influence of knowledge of respiratory diseases (KRD) and perceived pulmonary function risks (PFR) on smoking cessation attitudes (SCA) among adults in Klang Valley, Malaysia. Utilizing a quantitative research design and structured questionnaires, data were collected from a sample of 286 participants and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that PFR significantly and positively predicts smoking cessation attitudes, while KRD demonstrates a significant but negative association. These findings suggest that although awareness of respiratory diseases is essential, it may not be sufficient to encourage smoking cessation without the presence of motivational or supportive elements. Furthermore, socio-demographic factors, such as age, education level, and income, moderate the effects of KRD and PFR on cessation attitudes, enhancing the explanatory power of the model. Gender, however, showed no significant moderating effect. The study concludes that effective smoking cessation interventions should not only increase knowledge but also bolster self-efficacy and be tailored to demographic contexts. These insights contribute to the development of more targeted, effective public health strategies aimed at reducing smoking prevalence and promoting cessation efforts in diverse populations.